Teaching Strategy Used in Teaching Speaking Skill at Universitas Lakidende Unaaha - Nurwanti, Nurwanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
Improving the students’ speaking skill requires the appropriate strategies. This research aims to describe the kind of strategies which used by lecturers in teaching speaking on the fourth semester students of English Education Department at Lakidende Unaaha University. The instrument of this research is observation sheet. The subjects of this research were two lecturers of English Education Department who teaching speaking IV course at Lakidende Unaaha University. The data was collected by observing the lecturers. This research involved data condensation, data display, and drawing the conclusion as the procedure of data analysis. There are five teaching strategies used by lecturers in teaching speaking as result of the research, those are role play, presentation, drilling, language games, answer and question, and storytelling. The conclusion of research is, there are five strategies used by the speaking lecturers to teach the fourth semester students of English Education Department at Lakidende Unaaha University, namely Presentation, Drilling, Asking and Answering, Role Play, and Storytelling. Also, it is suggested to the speaking lecturers and teachers for choosing the appropriate teaching strategy and create various communicative, creative, and effective strategies to be implemented in teaching speaking, therefore, the teaching objectives can be achieved.